Effect of phase breaking on ac transport through a quantum dot dimer - Au Yeung, T. C. (2018)
The ac response of a coupled double quantum dot system involving a phase-breaking effect is studied. We calculate the ac conductance based on the nonequilibrium Green’s-function formalism. Some parasitic and gate capacitances are included in our model, thus the displacement current is considered, and the overall charge and current conservation are fulfilled. In our results the double resonant structure of the conductance is observed. We find that the electron-phonon interaction has a significant effect on the ac conductance both for low and high temperatures. Due to the phase-breaking effect of electron-phonon scattering, the resonant conductance peak is suppressed very seriously, and the second peak of the ac conductance may disappear completely, However, for the nonresonant situation, the conductance is enhanced for small frequencies. Furthermore, we study the effect of the capacitances on the ac conductance, and find that, for small frequencies, the capacitances have a small effect on the real part of the admittance. On the imaginary part of the admittance, all the capacitances except for the interdot capacitance have a considerable effect. For high frequencies all the capacitances have a considerable effect on the ac conductance.